Estudo da coordenação do processo de projeto arquitetônico em escritório de pequeno porte - Permonian, Raquel Ragonesi (Universidade Federal de São Carlos, 2016)
It is noticed in the last years a prominent growth in the national construction industry which has driven to an increase in competitiveness among its professionals. These new levels of competitiveness have led professionals to study possible innovations in the design process to create more efficient and cost effective planning methods. In general, architectural designers choose to develop their products using 2D design software. These tools are often able to meet the minimum representational requirements. However, technological breakthroughs have brought up new methods that are capable of adding quality to the final product, namely the executive project. Therefore, this study sought the theoretical background to present a review about concepts in 2D design process and the context of its coordination. As complement of that, the study aims to reveal possible qualitative increments to the project phases through the use of performance flowcharts of the existing steps inside the studied company, which takes into consideration the current scenario surrounding technologies in Brazil. This approach required the development of case studies to assess the coordination of architectural design process typology adopted in small office. Three projects of different sizes, based on the most commonly found typology in the studied company, were chosen in order to conceptualize the development of the design process. Based on that, the case studies were produced and evaluated to yield proposals for new studies regarding coordinative improvements in the design process. These studies focus an ideal performance model for design project management. Thus, the noticeable outcome of this study is that the target company must incorporate new methods to refine the design process once it presents noncompliant quality and excessive rework due to the lack of compatibility among projects. In addition, another evident fact affecting the product quality is that employees of this company deal with a high demand of parallel activities which reduces their productivity and consequently decreases the quality of the final product.
Study of the coordination of the architectural design process in small office
Keywords: Gestão do processo de projeto; Qualidade do processo de projeto; Coordenação de projeto; Processo de projeto arquitetônico; Design process management; Design process quality; Project coordination; Architectural design process; ENGENHARIAS::ENGENHARIA CIVIL